2015
DOI: 10.1016/j.actbio.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability and biological property evaluation of plasma sprayed hydroxyapatite coatings for orthopedic and dental applications

Abstract: In this work we have investigated the effects of strontium (Sr) dopant on in vitro protein release kinetics and in vivo osteogenic properties of plasma sprayed hydroxyapatite (HA) coatings, along with their dissolution behavior. Plasma sprayed HA coatings are widely used in load-bearing implants. Apart from osseointegration, the new generation of HA coating is expected to deliver biomolecules and/or drugs that can induce osteoinduction. This paper reports the preparation of crystalline and amorphous HA coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(94 citation statements)
references
References 33 publications
3
91
0
Order By: Relevance
“…However, with the rapid development of surface technology, HA coatings deposited by using surface technology on a metal substrate provide excellent biocompatibility and good mechanical properties. The plasma spraying technique is a common method for depositing HA coating on metal implants [4][5][6]. However, the overheating of HA particles in the plasma jet can cause the decomposition of the HA powders.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the rapid development of surface technology, HA coatings deposited by using surface technology on a metal substrate provide excellent biocompatibility and good mechanical properties. The plasma spraying technique is a common method for depositing HA coating on metal implants [4][5][6]. However, the overheating of HA particles in the plasma jet can cause the decomposition of the HA powders.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) is commonly applied in PS processes. Vahabzadeh et al reported that both stability and chemistry can be influenced significantly in vivo and in vitro by the plasma-sprayed HA coatings on Ti implants (Vahabzadeh, Roy, Bandyopadhyay, & Bose, 2015). But the loss of crystallinity of HA during spraying cannot be ignored and invokes further research studies (Zyman, Cao, & Zhang, 1993).…”
Section: Polyetheretherketonementioning
confidence: 99%
“…Some works [7,[41][42][43] observed the deposition of different kinds of HA coating (with or without reinforcements) on Ti and Ti based alloys using other methods, such as hydrothermal synthesis, electrodeposition, radio frequency sputtering, and plasma spray. These methods made it possible to obtain rather high quality coatings on Ti and Ti based substrates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%